Ecotoxicological evaluation of the immunocompetence of two bivalves species (Mya arenaria and Mytilus edulis) in the Saguenay Fjord including a salinity gradient - A. Beaudry; E. Lacaze; A. Jobin-Piché; S. Masson; M. Auffret; P. Brousseau; M. Fournier (MDPI AG, 2016)
Not available